High-molecular-weight PE (polyethylene) plastic pipe and production process thereof

By introducing functionalized olefin graft copolymers, modified silicon nitride fibers, and composite hollow glass microspheres into high molecular weight polyethylene (PE) plastic pipes, the problems of insufficient pressure resistance and creep resistance of PE under harsh working conditions are solved, and the mechanical properties and anti-aging properties of the pipes are improved.

CN120944222APending Publication Date: 2025-11-14HANGZHOU JINTAI PLASTIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511391590.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

High molecular weight polyethylene (HMWPE) is insufficient in pressure resistance, creep resistance, and mechanical strength in engineering scenarios such as deep-sea water transportation, high-pressure slurry transportation, or municipal pipelines buried at great depths. Furthermore, it is prone to aging and degradation during long-term use, leading to a decline in the mechanical properties of the pipeline.

Method used

High molecular weight PE plastic pipes are prepared by combining functionalized olefin graft copolymers, modified silicon nitride fibers, and composite hollow glass microspheres through a specific process. The functionalized olefin graft copolymers introduce polylactic acid side chains into the polyethylene main chain, the modified silicon nitride fibers undergo oxythermal crosslinking treatment, and the composite hollow glass microspheres have nano-titanium dioxide and zinc oxide layers attached to their surface to enhance their UV and IR resistance.

Benefits of technology

It significantly improves the mechanical properties and anti-aging properties of high molecular weight PE plastic pipes, enhances the tensile properties, impact resistance, and UV-IR resistance of the pipes, and extends their service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of high molecular materials, and discloses a high molecular weight PE plastic pipe and a production process thereof. The PE plastic pipe comprises the following raw materials in parts by weight: 70-80 parts of ultra-high molecular weight polyethylene, 8-12 parts of a functionalized olefin graft copolymer, 5-8 parts of modified silicon nitride fibers, 5-8 parts of composite hollow glass beads, 0.5-0.8 part of an anti-aging agent, 2-3 parts of a dispersing agent and 4 parts of color master batches, the production process provided by the invention comprises the following working procedures: premixing raw materials, preheating an extruder, preheating a traction pipe, co-extruding, performing vacuum sizing, performing pipe traction and performing online adjustment. The high-molecular-weight PE plastic pipe prepared by the invention has excellent mechanical properties and also has excellent ultraviolet and infrared aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a high molecular weight PE plastic pipe and its production process. Background Technology

[0002] High molecular weight polyethylene (HMWPE) typically refers to linear high-density polyethylene with a viscosity-average molecular weight exceeding 500,000. It is a high-performance thermoplastic engineering plastic, particularly valuable in piping systems. Due to its extremely high molecular weight, regular molecular chain structure, and unique aggregation characteristics, this material exhibits excellent wear resistance, corrosion resistance, self-lubrication, impact resistance, and stress cracking resistance. These properties make it especially suitable for pipeline applications under harsh working conditions.

[0003] In the grain, coal, chemical, and municipal engineering industries, ultra-high molecular weight polyethylene (UHMWPE) pipes are widely used to transport particles, powders, slurries, and corrosive media, such as grain transportation, mineral slurry transportation, chemical fluid transmission, and urban drainage. Their superior overall performance significantly reduces pipe wear and blockage risks, extends service life, and decreases maintenance frequency.

[0004] However, in more demanding engineering scenarios, such as deep-sea water transport, high-pressure slurry transportation, or deep-buried municipal pipelines, high molecular weight polyethylene (HMWPE) still falls short in terms of long-term pressure resistance, creep resistance, and mechanical strength. Furthermore, as a polymer material, HMWPE is prone to aging and degradation during long-term use, leading to a decline in the mechanical properties of the pipeline or even its failure, resulting in operational risks and economic losses. Summary of the Invention

[0005] To address the shortcomings mentioned in the background section, the present invention aims to provide a high molecular weight PE plastic pipe and its manufacturing process.

[0006] The objective of this invention can be achieved through the following technical solutions: A high molecular weight PE plastic pipe, characterized in that it comprises the following raw materials in parts by weight: 70-80 parts of ultra-high molecular weight polyethylene, 8-12 parts of functionalized olefin graft copolymer, 5-8 parts of modified silicon nitride fiber, 5-8 parts of composite hollow glass microspheres, 0.5-0.8 parts of anti-aging agent, 2-3 parts of dispersant, and 4 parts of color masterbatch. The functionalized olefin graft copolymer is obtained by first protecting the hydroxyl groups with triisobutylaluminum to synthesize a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer, and then introducing polylactic acid side chains into the copolymer using hydroxyl ring-opening L-lactide. The modified silicon nitride fiber is a silicon nitride fiber that has undergone thermo-oxidative crosslinking treatment; The composite hollow glass microspheres are obtained by first attaching nano-titanium dioxide to the surface of hollow glass microspheres etched by saturated calcium hydroxide solution, then growing titanium dioxide nanorods on the titanium dioxide layer using tetrabutyl titanate as a silicon source, and finally forming a nano-zinc oxide coating layer on the titanium dioxide using zinc acetate as a zinc source.

[0007] Preferably, the preparation process of the functionalized olefin graft copolymer includes the following steps: A1: In a nitrogen atmosphere, triisobutylaluminum, undecenol, toluene, ethyl-bridged diindenyl dizirconia, and hexene are added to a reaction vessel. Ethylene is introduced to control the pressure in the reaction vessel, the temperature is controlled at 30-35℃, and the reaction is maintained at this temperature for 10-20 minutes. The hydroxyl groups are deprotected with acidic ethanol to obtain a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer. A2: The hydroxyl-functionalized ethylene-hexene-undecenol terpolymer and toluene were placed in a reaction vessel and heated to 100°C to dissolve completely. The temperature was then lowered to 80°C. Toluene, L-lactide, and 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene were then added to the reaction vessel and the temperature was lowered to 50-60°C. The mixture was stirred and reacted for 4-6 hours. The mixture was precipitated with anhydrous ethanol, filtered, washed multiple times with anhydrous ethanol, and dried in a vacuum oven to obtain the functionalized olefin graft copolymer.

[0008] Preferably, ethylene is introduced into A1 to control the pressure in the reactor to 1 atm, and the weight ratio of triisobutylaluminum, undecenol, ethyl-bridged diindene dizirconia, and hexene is 140-160:125-135:0.001:40-50. The weight ratio of hydroxyl-functionalized ethylene-hexene-undecenol terpolymer, L-lactide, and 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene added in A2 is 100-110:40-50:0.1.

[0009] Preferably, the preparation process of the modified silicon nitride fiber includes the following steps: B1: Methyldichlorosilane, dimethyldichlorosilane, and n-hexane are mixed and added to a reactor. Ammonia gas is introduced into the reactor under a nitrogen atmosphere to control the pressure. The reaction is considered complete when the gas outlet is alkaline, as indicated by red litmus paper. The mixture is filtered and distilled to obtain silazane oligomers. The silazane oligomers are placed in a flask under flowing nitrogen and heated to 360-400℃. The temperature is maintained for 10-14 hours. After cooling, silicon nitride precursors are obtained. B2: Add the silicon nitride precursor to the spinning machine, heat it to 140-145℃ under a nitrogen atmosphere for melt spinning to obtain silicon nitride fiber, put the silicon nitride fiber filament into an oven connected to air, slowly heat it to 120-130℃ and keep it at that temperature for 12-14h to obtain silicon nitride cross-linked filament. B3. Place the silicon nitride crosslinked fiber into a high-temperature tube furnace and pyrolyze it under a nitrogen atmosphere. First, raise the temperature from room temperature to 500℃ at a rate of 5℃ / min, then raise it from 500℃ to 900℃ at a rate of 3℃ / min, and finally adjust the heating rate to 4℃ / min to raise it from 900℃ to 1400℃. Hold the temperature for 2 hours, and then treat it at 1500℃ for 1-2 hours under an air atmosphere to obtain modified silicon nitride fiber.

[0010] Preferably, the pressure of the ammonia gas introduced into the reactor in B1 is 0.1 MPa, and the weight ratio of methyldichlorosilane to dimethyldichlorosilane is 10:5-6. The nitrogen flow rate in B2 is maintained at 0.1 L / min.

[0011] Preferably, the preparation process of the composite hollow glass microspheres includes the following steps: C1: Dissolve nano-titanium dioxide powder in deionized water to obtain nano-titanium dioxide solution. Pretreat hollow glass microspheres with saturated calcium hydroxide solution at 90℃ for 8h. Add nano-titanium dioxide solution and stir at 80-90℃ for 6-8h. Dry to obtain nano-titanium dioxide surface modified hollow glass microspheres. C2: Nano-titanium dioxide surface-modified hollow glass microspheres and tetrabutyl titanate are mixed together, hydrochloric acid is added, and the mixture is heated at 150-170℃ for 6-10 hours. After cooling and filtration, the mixture is washed alternately with deionized water and anhydrous ethanol and dried to obtain modified hollow glass microspheres. C3: Mix modified hollow glass microspheres, polyvinylpyrrolidone, and deionized water, sonicate for 20 minutes, heat to 60-90℃, adjust pH to 9-12 with sodium hydroxide, add zinc acetate and sodium dodecyl sulfonate, keep warm for 4-6 hours, filter, wash, and dry to obtain composite hollow glass microspheres.

[0012] Preferably, the concentration of the nano-titanium dioxide solution in C1 is 5 wt%, and the weight ratio of the pretreated hollow glass microspheres to the nano-titanium dioxide solution is 1:20-22. The hydrochloric acid concentration in C2 is 30wt%, and the weight ratio of nano-titanium dioxide surface-modified hollow glass microspheres, tetrabutyl titanate, and hydrochloric acid is 1:3-5:60-70. The weight ratio of modified hollow glass microspheres, polyvinylpyrrolidone, zinc acetate, and sodium dodecyl sulfonate in C3 is 1:0.02:2-3:0.2-0.5.

[0013] Preferably, the anti-aging agent is any one of styrene-phenol and 2,2,4-trimethyl-1,2-dihydroquinoline polymer; The dispersant is any one of polyethylene wax, polyethylene glycol, or polypropylene glycol.

[0014] Preferably, the production process of the high molecular weight PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 120-130℃ and stir for 30-60 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 140-160℃ for 3-4 hours, then heat it to 180-200℃ for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0015] The beneficial effects of this invention are: (1) This invention adds a functionalized olefin graft copolymer. First, triisobutylaluminum is used to protect the hydroxyl groups, and ethylene and hexene are used as comonomers to obtain a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer. Then, the hydroxyl groups are used to initiate the ring-opening polymerization of L-lactide, thereby grafting polylactic acid side chains onto the polyethylene backbone. The insertion of hexene disrupts the regular structure of the ethylene chain, reduces the crystallinity of the material, and increases the flexibility of the molecular chain, which is beneficial to subsequent hot processing and improved toughness. At the same time, the rigid polylactic acid segments can also act as physical crosslinking points in the material, thereby improving the tensile properties of the pipe.

[0016] (2) This invention also incorporates oxygen-thermal crosslinking treated silicon nitride fibers. Silicon nitride is a highly covalent compound with high hardness, high strength at high temperatures, good thermal shock resistance, high oxidation resistance, high insulation, and good elastic modulus. The Si-H bonds in the oxygen-thermal crosslinking treated silicon nitride fibers are transformed into a Si-O-Si bridged structure, achieving an infusible and insoluble state. The three-stage heating process makes the silicon nitride fibers more compact, which is beneficial for the stable bonding between the fibers and PE pipes.

[0017] (3) The polylactic acid segments of the functionalized olefin graft copolymer and the Si-O-Si bridging structure of the modified silicon nitride fiber can form a three-dimensional network cross-linked structure, which plays a synergistic role and greatly improves the mechanical properties of high molecular weight PE plastic pipe.

[0018] (4) This invention utilizes saturated calcium hydroxide solution to corrode nano-titanium dioxide onto the surface of hollow glass microspheres. Then, using tetrabutyl titanate as the silicon source and hydrochloric acid as the growth control agent, titanium dioxide nanorods are grown on the nano-titanium dioxide layer. Finally, zinc acetate is used as the zinc source to attach a continuous and dense zinc oxide layer to the surface of the titanium dioxide nanorods. Both nano-zinc oxide and nano-titanium dioxide are wide-bandgap semiconductors. Nano-titanium dioxide has strong absorption capacity in the mid-wave ultraviolet region, and the nanorod structure can generate effective scattering, enhancing the reflectivity of near-infrared light. Nano-zinc oxide has strong absorption capacity in the long-wave ultraviolet region and high reflectivity in the infrared region. The combination of the two has a synergistic effect, improving the response range and endowing the composite hollow glass microspheres with strong anti-ultraviolet and infrared properties, thus improving the anti-aging performance of high molecular weight PE plastic pipes. The hollow glass microspheres have a soda lime borosilicate shell and a closed hollow interior, possessing advantages such as light weight, heat insulation, wear resistance, and chemical corrosion resistance, which also improves the mechanical properties of the pipe to a certain extent.

[0019] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0020] The technical solutions described below in conjunction with the embodiments will be clearly and completely described. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1: The preparation process of functionalized olefin graft copolymers includes the following steps: A1: In a nitrogen atmosphere, 14g of triisobutylaluminum, 12.5g of undecenol, 50mL of toluene, 0.0001g of bridged metallocene catalyst ethyl-bridged diindenyl dichloride, and 4g of hexene were added to a reactor. Ethylene was introduced to control the pressure in the reactor at 1 atm, and the reaction was carried out at 30℃ for 10 min to obtain a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer. A2: 50g of hydroxyl-functionalized ethylene-hexene-undecenol terpolymer and 100mL of toluene were placed in a reaction vessel and heated to 100℃ to dissolve completely. The temperature was then lowered to 80℃. 50mL of toluene, 20g of L-lactide, and 0.05g of 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene were mixed and added to the reaction vessel. The temperature was lowered to 50℃ and stirred for 5h. The mixture was precipitated with anhydrous ethanol, filtered, washed multiple times with anhydrous ethanol, and dried in a vacuum oven to obtain the functionalized olefin graft copolymer.

[0022] The preparation process of modified silicon nitride fibers includes the following steps: B1: 10g of methyldichlorosilane, 5g of dimethyldichlorosilane, and 100mL of n-hexane were mixed and added to a reaction vessel. Ammonia gas was introduced into the reaction vessel under a nitrogen atmosphere. The pressure of the reaction vessel was controlled at 0.1MPa. The reaction was considered complete when the gas outlet was alkaline, as indicated by testing with red litmus paper. The mixture was filtered and distilled to obtain silazane oligomers. The silazane oligomers were placed in a flask with nitrogen flowing through it and heated to 360℃. The temperature was maintained for 10h. After cooling, silicon nitride precursors were obtained. B2: Add the silicon nitride precursor to the spinning machine, heat it to 140°C under a nitrogen atmosphere for melt spinning, and control the nitrogen flow rate at 0.1L / min to obtain silicon nitride fibers. Place the silicon nitride fiber filaments in an oven connected to air, slowly heat it to 120°C and keep it at that temperature for 12 hours to obtain silicon nitride cross-linked filaments. B3. Place the silicon nitride crosslinked fiber into a high-temperature tube furnace and pyrolyze it under a nitrogen atmosphere. First, raise the temperature from room temperature to 500℃ at a rate of 5℃ / min, then raise it from 500℃ to 900℃ at a rate of 3℃ / min, and finally adjust the heating rate to 4℃ / min to raise it from 900℃ to 1400℃. Hold the temperature for 2 hours, and then treat it at 1500℃ for 1 hour under an air atmosphere to obtain modified silicon nitride fiber.

[0023] The preparation process of composite hollow glass microspheres includes the following steps: C1: Dissolve nano-titanium dioxide powder in deionized water to obtain a 5wt% nano-titanium dioxide solution. Pretreat 5g of hollow glass microspheres with saturated calcium hydroxide solution at 90℃ for 8h. Add 100g of nano-titanium dioxide solution and stir at 80℃ for 6h. Dry to obtain nano-titanium dioxide surface modified hollow glass microspheres. C2: Mix 5g of nano-titanium dioxide surface-modified hollow glass microspheres and 15g of tetrabutyl titanate, add 55mL of 30wt% hydrochloric acid, heat at 150℃ for 6h, cool, filter, wash alternately with deionized water and anhydrous ethanol, and dry to obtain modified hollow glass microspheres. C3: Mix 5g of modified hollow glass microspheres, 0.1g of polyvinylpyrrolidone, and 100mL of deionized water, sonicate for 20min, heat to 60℃, adjust pH to 9-12 with sodium hydroxide, add 10g of zinc acetate and 1g of sodium dodecyl sulfonate, keep warm for 4h, filter, wash, and dry to obtain composite hollow glass microspheres.

[0024] Example 2: The preparation process of functionalized olefin graft copolymers includes the following steps: A1: In a nitrogen atmosphere, 15g of triisobutylaluminum, 13g of undecenol, 50mL of toluene, 0.0001g of bridged metallocene catalyst ethyl-bridged diindenyl dichloride, and 4.5g of hexene were added to a reactor. Ethylene was introduced to control the pressure in the reactor at 1 atm, and the reaction was carried out at 33℃ for 15min to obtain a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer. A2: 35g of hydroxyl-functionalized ethylene-hexene-undecenol terpolymer and 100mL of toluene were placed in a reaction vessel and heated to 100℃ to dissolve completely. The temperature was then lowered to 80℃. 50mL of toluene, 15g of L-lactide, and 0.04g of 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene were added to the reaction vessel and the mixture was cooled to 55℃ and stirred for 5h. The mixture was then precipitated with anhydrous ethanol, filtered, washed multiple times with anhydrous ethanol, and dried in a vacuum oven to obtain the functionalized olefin graft copolymer.

[0025] The preparation process of modified silicon nitride fibers includes the following steps: B1: 10g of methyldichlorosilane, 5.5g of dimethyldichlorosilane, and 100mL of n-hexane were mixed and added to a reaction vessel. Ammonia gas was introduced into the reaction vessel under a nitrogen atmosphere. The pressure of the reaction vessel was controlled at 0.1MPa. The reaction was considered complete when the gas outlet was alkaline, as indicated by testing with red litmus paper. The mixture was filtered and distilled to obtain silazane oligomers. The silazane oligomers were placed in a flask with nitrogen flowing through it and heated to 380℃. The temperature was maintained for 12h. After cooling, silicon nitride precursors were obtained. B2: Add the silicon nitride precursor to the spinning machine, heat it to 143°C under a nitrogen atmosphere for melt spinning, and control the nitrogen flow rate at 0.1L / min to obtain silicon nitride fibers. Place the silicon nitride fiber filaments in an oven connected to air, slowly heat it to 125°C and keep it at that temperature for 12 hours to obtain silicon nitride cross-linked filaments. B3. Place the silicon nitride crosslinked fiber into a high-temperature tube furnace and pyrolyze it under a nitrogen atmosphere. First, raise the temperature from room temperature to 500℃ at a rate of 5℃ / min, then raise it from 500℃ to 900℃ at a rate of 3℃ / min, and finally adjust the heating rate to 4℃ / min to raise it from 900℃ to 1400℃. Hold the temperature for 2 hours, and then treat it at 1500℃ for 1.5 hours under an air atmosphere to obtain modified silicon nitride fiber.

[0026] The preparation process of composite hollow glass microspheres includes the following steps: C1: Dissolve nano-titanium dioxide powder in deionized water to obtain a 5wt% nano-titanium dioxide solution. Pretreat 5g of hollow glass microspheres with saturated calcium hydroxide solution at 90℃ for 8h. Add 105g of nano-titanium dioxide solution and stir at 85℃ for 7h. Dry to obtain nano-titanium dioxide surface modified hollow glass microspheres. C2: Mix 5g of nano-titanium dioxide surface-modified hollow glass microspheres and 20g of tetrabutyl titanate, add 60mL of 30wt% hydrochloric acid, heat at 160℃ for 8h, cool, filter, wash alternately with deionized water and anhydrous ethanol, and dry to obtain modified hollow glass microspheres. C3: Mix 5g of modified hollow glass microspheres, 0.1g of polyvinylpyrrolidone, and 100mL of deionized water, sonicate for 20min, heat to 75℃, adjust the pH to 9-12 with sodium hydroxide, add 12.5g of zinc acetate and 1.8g of sodium dodecyl sulfonate, keep warm for 5h, filter, wash, and dry to obtain composite hollow glass microspheres.

[0027] Example 3: The preparation process of functionalized olefin graft copolymers includes the following steps: A1: In a nitrogen atmosphere, 16g of triisobutylaluminum, 13.5g of undecenol, 50mL of toluene, 0.0001g of bridged metallocene catalyst ethyl-bridged diindenyl dichloride, and 5g of hexene were added to a reactor. Ethylene was introduced to control the pressure in the reactor at 1 atm, and the reaction was carried out at 35℃ for 20min to obtain a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer. A2: 55g of hydroxyl-functionalized ethylene-hexene-undecenol terpolymer and 100mL of toluene were placed in a reaction vessel and heated to 100℃ to dissolve completely. The temperature was then lowered to 80℃. 50mL of toluene, 15g of L-lactide, and 0.05g of 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene were added to the reaction vessel and the mixture was cooled to 60℃ and stirred for 4 hours. The mixture was then precipitated with anhydrous ethanol, filtered, washed multiple times with anhydrous ethanol, and dried in a vacuum oven to obtain the functionalized olefin graft copolymer.

[0028] The preparation process of modified silicon nitride fibers includes the following steps: B1: 10g of methyldichlorosilane, 6g of dimethyldichlorosilane, and 100mL of n-hexane were mixed and added to a reaction vessel. Ammonia gas was introduced into the reaction vessel under a nitrogen atmosphere. The pressure of the reaction vessel was controlled at 0.1MPa. The reaction was considered complete when the gas outlet was alkaline, as indicated by testing with red litmus paper. The mixture was filtered and distilled to obtain silazane oligomers. The silazane oligomers were placed in a flask with nitrogen flowing through it and heated to 400℃. The temperature was maintained for 14h. After cooling, silicon nitride precursors were obtained. B2: Add the silicon nitride precursor to the spinning machine, heat it to 145°C under a nitrogen atmosphere for melt spinning, and control the nitrogen flow rate at 0.1L / min to obtain silicon nitride fibers. Place the silicon nitride fiber filaments in an oven connected to air, slowly heat it to 130°C and keep it at that temperature for 14 hours to obtain silicon nitride cross-linked filaments. B3. Place the silicon nitride crosslinked fiber into a high-temperature tube furnace and pyrolyze it under a nitrogen atmosphere. First, raise the temperature from room temperature to 500℃ at a rate of 5℃ / min, then raise it from 500℃ to 900℃ at a rate of 3℃ / min, and finally adjust the heating rate to 4℃ / min to raise it from 900℃ to 1400℃. Hold the temperature for 2 hours, and then treat it at 1500℃ for 1.5 hours under an air atmosphere to obtain modified silicon nitride fiber.

[0029] The preparation process of composite hollow glass microspheres includes the following steps: C1: Dissolve nano-titanium dioxide powder in deionized water to obtain a 5wt% nano-titanium dioxide solution. Pretreat 5g of hollow glass microspheres with saturated calcium hydroxide solution at 90℃ for 8h. Add 110g of nano-titanium dioxide solution and stir at 90℃ for 8h. Dry to obtain nano-titanium dioxide surface-modified hollow glass microspheres. C2: Mix 5g of nano-titanium dioxide surface-modified hollow glass microspheres with 25g of tetrabutyl titanate, add 65mL of 30wt% hydrochloric acid, heat at 170℃ for 10h, cool, filter, wash alternately with deionized water and anhydrous ethanol, and dry to obtain modified hollow glass microspheres. C3: Mix 5g of modified hollow glass microspheres, 0.1g of polyvinylpyrrolidone, and 100mL of deionized water, sonicate for 20min, heat to 90℃, adjust pH to 9-12 with sodium hydroxide, add 15g of zinc acetate and 2.5g of sodium dodecyl sulfonate, keep warm for 6h, filter, wash, and dry to obtain composite hollow glass microspheres.

[0030] Example 4: A high molecular weight PE plastic pipe, comprising the following raw materials in parts by weight: 70 parts ultra-high molecular weight polyethylene, 8 parts functionalized olefin graft copolymer, 5 parts modified silicon nitride fiber, 5 parts composite hollow glass microspheres, 0.5 parts styrene-phenol, 2 parts polyethylene wax, and 4 parts color masterbatch; the functionalized olefin graft copolymer, the modified silicon nitride fiber, and the composite hollow glass microspheres are prepared by the method in Example 1; the production process of the high molecular weight PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 120°C and stir for 30 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 140°C for 3 hours, then heat it to 180°C for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0031] Example 5: A high molecular weight PE plastic pipe, comprising the following raw materials in parts by weight: 75 parts ultra-high molecular weight polyethylene, 10 parts functionalized olefin graft copolymer, 6.5 parts modified silicon nitride fiber, 6.5 parts composite hollow glass microspheres, 0.7 parts styrene-phenol, 2.5 parts polyethylene wax, and 4 parts color masterbatch; the functionalized olefin graft copolymer, the modified silicon nitride fiber, and the composite hollow glass microspheres are prepared by the method in Example 2; the production process of the high molecular weight PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 125°C and stir for 45 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 150°C for 3.5 hours, then heat it to 190°C for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0032] Example 6: A high molecular weight PE plastic pipe, comprising the following raw materials in parts by weight: 80 parts ultra-high molecular weight polyethylene, 12 parts functionalized olefin graft copolymer, 8 parts modified silicon nitride fiber, 8 parts composite hollow glass microspheres, 0.8 parts styrene-phenol, 3 parts polyethylene wax, and 4 parts color masterbatch; the functionalized olefin graft copolymer, the modified silicon nitride fiber, and the composite hollow glass microspheres are prepared by the method in Example 3; the production process of the high molecular weight PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 130°C and stir for 60 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 160°C for 4 hours, then heat it to 200°C for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0033] Comparative Example 1: A PE plastic pipe comprising the following raw materials in parts by weight: 75 parts ultra-high molecular weight polyethylene, 6.5 parts modified silicon nitride fiber, 6.5 parts composite hollow glass microspheres, 0.7 parts styrene-phenol, 2.5 parts polyethylene wax, and 4 parts color masterbatch; the modified silicon nitride fiber and the composite hollow glass microspheres are prepared by the method in Example 2; the production process of the PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 125°C and stir for 45 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 150°C for 3.5 hours, then heat it to 190°C for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0034] Comparative Example 2: A PE plastic pipe comprising the following raw materials in parts by weight: 75 parts ultra-high molecular weight polyethylene, 10 parts functionalized olefin graft copolymer, 6.5 parts silicon nitride fiber, 6.5 parts composite hollow glass microspheres, 0.7 parts styrene-phenol, 2.5 parts polyethylene wax, and 4 parts color masterbatch; the functionalized olefin graft copolymer and the composite hollow glass microspheres are prepared by the method in Example 2; the production process of the PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 125°C and stir for 45 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 150°C for 3.5 hours, then heat it to 190°C for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0035] Comparative Example 3: A PE plastic pipe comprising the following raw materials in parts by weight: 75 parts ultra-high molecular weight polyethylene, 10 parts functionalized olefin graft copolymer, 6.5 parts modified silicon nitride fiber, 6.5 parts hollow glass microspheres, 0.7 parts styrene-phenol, 2.5 parts polyethylene wax, and 4 parts color masterbatch; the functionalized olefin graft copolymer and the modified silicon nitride fiber are prepared by the method in Example 2; the production process of the PE plastic pipe includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 125°C and stir for 45 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 150°C for 3.5 hours, then heat it to 190°C for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.

[0036] Performance testing 1. Tensile properties and elongation at break: According to GB / T 1040.1-2018 "Determination of tensile properties of plastics - Part 1: General", dumbbell-shaped specimens with a length of 170 mm were extruded from the molten material of Examples 4-6 and Comparative Examples 1-3 using a template. The specimens were mounted on a universal testing machine with their axis aligned with the direction of tensile stress. The stress-strain curves of the specimens were recorded until the specimens broke. The tensile strength and elongation at break were calculated respectively. The results are shown in Table 1.

[0037] 2. Bending strength: According to GB / T 9341-2008 "Determination of bending properties of plastics", the molten material from Examples 4-6 and Comparative Examples 1-3 was extruded into strips with a size of 80mm×10mm×4mm using a template. The strips were installed on a universal testing machine and bent at a speed of 2mm / min. The bending strength was calculated, and the results are shown in Table 1.

[0038] 3. Impact strength: According to GB / T 1843-2008 "Determination of impact strength of plastic cantilever beam", the molten material from Examples 4-6 and Comparative Examples 1-3 was extruded into 80mm×10mm×4mm specimens using a template. The specimens were tested using an impact testing machine. The friction loss and corrected absorbed energy were determined according to GB / T 21189-2007, and the impact strength was calculated. The results are shown in Table 1.

[0039] Table 1. Statistical table of mechanical properties of samples prepared in Examples 4-6 and Comparative Examples 1-3

[0040] As shown in Table 1, Examples 4-6 exhibited excellent mechanical properties. Comparative Example 1, which did not incorporate functionalized olefin graft copolymers, showed significantly lower tensile strength, elongation at break, and flexural strength compared to the other examples and comparative examples. Comparative Example 2, which did not modify silicon nitride fibers, had the worst impact strength among all examples and comparative examples, and its tensile strength, elongation at break, and flexural strength were also significantly lower than the other groups. Comparative Example 3, which did not modify hollow glass microspheres, showed only slightly lower impact strength compared to Examples 4-6 and Comparative Example 1.

[0041] 4. Light stability test: The molten material from Examples 4-6 and Comparative Examples 1-3 was extruded using a template to form dumbbell-shaped strips with a length of 170 mm. The strips were subjected to light aging according to GB / T 16422.2-2022 "Laboratory Light Source Exposure Test Methods for Plastics - Part 2: Xenon Arc Lamp". The tensile strength was then determined using the method in GB / T 1040.1-2018. The results are shown in Table 2.

[0042] Table 2. Statistical table of tensile properties of samples obtained from Examples 4-6 and Comparative Examples 1-3 after artificial aging.

[0043] As shown in Table 2, Comparative Example 3, without modified hollow glass microspheres, retained only 36% of its tensile strength after aging under an artificial xenon arc lamp for 40 hours, which is about half that of the other examples and comparative examples. This indicates that the structure of the nano zinc oxide layer coated with the nano titanium dioxide layer contributes significantly to the UV-IR aging resistance of the high molecular weight PE plastic pipe.

[0044] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0045] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A high molecular weight PE plastic pipe, characterized in that, The raw materials include the following parts by weight: 70-80 parts of ultra-high molecular weight polyethylene, 8-12 parts of functionalized olefin graft copolymer, 5-8 parts of modified silicon nitride fiber, 5-8 parts of composite hollow glass microspheres, 0.5-0.8 parts of anti-aging agent, 2-3 parts of dispersant, and 4 parts of color masterbatch. The functionalized olefin graft copolymer is obtained by first protecting the hydroxyl groups with triisobutylaluminum to synthesize a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer, and then introducing polylactic acid side chains into the copolymer using hydroxyl ring-opening L-lactide. The modified silicon nitride fiber is a silicon nitride fiber that has undergone thermo-oxidative crosslinking treatment; The composite hollow glass microspheres are obtained by first attaching nano-titanium dioxide to the surface of hollow glass microspheres etched by saturated calcium hydroxide solution, then growing titanium dioxide nanorods on the titanium dioxide layer using tetrabutyl titanate as a silicon source, and finally forming a nano-zinc oxide coating layer on the titanium dioxide using zinc acetate as a zinc source.

2. The high molecular weight PE plastic pipe according to claim 1, characterized in that, The preparation process of the functionalized olefin graft copolymer includes the following steps: A1: In a nitrogen atmosphere, triisobutylaluminum, undecenol, toluene, ethyl-bridged diindenyl dizirconia, and hexene are added to a reaction vessel. Ethylene is introduced to control the pressure in the reaction vessel, the temperature is controlled at 30-35℃, and the reaction is maintained at this temperature for 10-20 minutes. The hydroxyl groups are deprotected with acidic ethanol to obtain a hydroxyl-functionalized ethylene-hexene-undecenol terpolymer. A2: The hydroxyl-functionalized ethylene-hexene-undecenol terpolymer and toluene were placed in a reaction vessel and heated to 100°C to dissolve completely. The temperature was then lowered to 80°C. Toluene, L-lactide, and 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene were then added to the reaction vessel and the temperature was lowered to 50-60°C. The mixture was stirred and reacted for 4-6 hours. The mixture was precipitated with anhydrous ethanol, filtered, washed multiple times with anhydrous ethanol, and dried in a vacuum oven to obtain the functionalized olefin graft copolymer.

3. The high molecular weight PE plastic pipe according to claim 2, characterized in that, Ethylene is introduced into A1 to control the pressure in the reactor to 1 atm. The weight ratio of added triisobutylaluminum, undecenol, ethyl-bridged diindene dizirconia, and hexene is 140-160:125-135:0.001:40-50. The weight ratio of hydroxyl-functionalized ethylene-hexene-undecenol terpolymer, L-lactide, and 7-methyl-1,5,7-triazabicyclo[4.4.0]-dec-5-ene added in A2 is 100-110:40-50:0.

1.

4. A high molecular weight PE plastic pipe according to claim 1, characterized in that, The preparation process of the modified silicon nitride fiber includes the following steps: B1: Methyldichlorosilane, dimethyldichlorosilane, and n-hexane are mixed and added to a reactor. Ammonia gas is introduced into the reactor under a nitrogen atmosphere to control the pressure. The reaction is considered complete when the gas outlet is alkaline, as indicated by red litmus paper. The mixture is filtered and distilled to obtain silazane oligomers. The silazane oligomers are placed in a flask under flowing nitrogen and heated to 360-400℃. The temperature is maintained for 10-14 hours. After cooling, silicon nitride precursors are obtained. B2: Add the silicon nitride precursor to the spinning machine, heat it to 140-145℃ under a nitrogen atmosphere for melt spinning to obtain silicon nitride fiber, put the silicon nitride fiber filament into an oven connected to air, slowly heat it to 120-130℃ and keep it at that temperature for 12-14h to obtain silicon nitride cross-linked filament. B3. Place the silicon nitride crosslinked fiber into a high-temperature tube furnace and pyrolyze it under a nitrogen atmosphere. First, raise the temperature from room temperature to 500℃ at a rate of 5℃ / min, then raise it from 500℃ to 900℃ at a rate of 3℃ / min, and finally adjust the heating rate to 4℃ / min to raise it from 900℃ to 1400℃. Hold the temperature for 2 hours, and then treat it at 1500℃ for 1-2 hours under an air atmosphere to obtain modified silicon nitride fiber.

5. A high molecular weight PE plastic pipe according to claim 4, characterized in that, In B1, the pressure of the ammonia gas introduced into the reactor is 0.1 MPa, and the weight ratio of methyldichlorosilane to dimethyldichlorosilane is 10:5-6. The nitrogen flow rate in B2 is maintained at 0.1 L / min.

6. A high molecular weight PE plastic pipe according to claim 1, characterized in that, The preparation process of the composite hollow glass microspheres includes the following steps: C1: Dissolve nano-titanium dioxide powder in deionized water to obtain nano-titanium dioxide solution. Pretreat hollow glass microspheres with saturated calcium hydroxide solution at 90℃ for 8h. Add nano-titanium dioxide solution and stir at 80-90℃ for 6-8h. Dry to obtain nano-titanium dioxide surface modified hollow glass microspheres. C2: Nano-titanium dioxide surface-modified hollow glass microspheres and tetrabutyl titanate are mixed together, hydrochloric acid is added, and the mixture is heated at 150-170℃ for 6-10 hours. After cooling and filtration, the mixture is washed alternately with deionized water and anhydrous ethanol and dried to obtain modified hollow glass microspheres. C3: Mix modified hollow glass microspheres, polyvinylpyrrolidone, and deionized water, sonicate for 20 minutes, heat to 60-90℃, adjust pH to 9-12 with sodium hydroxide, add zinc acetate and sodium dodecyl sulfonate, keep warm for 4-6 hours, filter, wash, and dry to obtain composite hollow glass microspheres.

7. A high molecular weight PE plastic pipe according to claim 6, characterized in that, The concentration of nano-titanium dioxide solution in C1 is 5wt%, and the weight ratio of pretreated hollow glass microspheres to nano-titanium dioxide solution is 1:20-22. The hydrochloric acid concentration in C2 is 30wt%, and the weight ratio of nano-titanium dioxide surface-modified hollow glass microspheres, tetrabutyl titanate, and hydrochloric acid is 1:3-5:60-70. The weight ratio of modified hollow glass microspheres, polyvinylpyrrolidone, zinc acetate, and sodium dodecyl sulfonate in C3 is 1:0.02:2-3:0.2-0.

5.

8. A high molecular weight PE plastic pipe according to claim 1, characterized in that, The anti-aging agent is any one of styrene-phenol and 2,2,4-trimethyl-1,2-dihydroquinoline polymer; The dispersant is any one of polyethylene wax, polyethylene glycol, or polypropylene glycol.

9. A manufacturing process for high molecular weight PE plastic pipes according to any one of claims 1-8, characterized in that, The process includes the following steps: S1: Weigh all the raw materials according to the formula weight parts, dry and remove moisture, put them into the mixer, control the mixing temperature at 120-130℃ and stir for 30-60 minutes, stop heating, and cool to obtain the premix; S2: Preheat the extruder to 150℃ for 3-4 hours, then heat it to 200℃ for 1 hour; S3: The molten material is extruded through an extruder and the traction tube is preheated so that the material can be completely adhered to it. For pipes with a specification of less than 160mm, the molten material is directly adhered to the surface of the pipe and the outer surface of the traction tube is preheated. For pipes with a specification of more than 160mm, the cross section and surface of the traction tube are preheated by butt joint. S4: The extruded molten material is introduced into the vacuum stenter by the traction machine and the traction continues, and the speed is gradually increased by starting synchronously; S5: Check the pipe's outer diameter and wall thickness and adjust them online. After the check meets the standard, turn on the inkjet printer and set the cutting length.